ANALISIS KELAYAKAN USAHA PETERNAKAN SAPI DI SAPI PERKASA FARM KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG - Kartika Dwi Jayanti; Adhona Bhajana Wijaya Negara (Bajang Institute, 2025)
This study aims to analyze the business feasibility of Aceh cattle farming at Sapi Perkasa Farm, located in Cot Geundreut Village, Samatiga District, West Aceh Regency. The business focuses on fattening Aceh cattle for the Qurban (sacrificial) market, with a 3-month rearing period conducted four times a year (4 cycles). The feasibility analysis uses several financial indicators, including Break Even Point (BEP), Benefit Cost Ratio (B/C), Return on Investment (ROI), and Revenue Cost Ratio (R/C). The results show that the cattle farming business is highly feasible. The BEP value is only 0.23 head, indicating that the business reaches the break-even point by selling just one head of cattle. Total revenue in one cycle reaches IDR 2,080,000,000 with a net profit of IDR 1,894,813,636. The B/C and R/C Ratios are both 11.23, reflecting very high operational efficiency. Meanwhile, the ROI reaches 382.78%, indicating a rapid return on investment and high profitability. Based on these findings, it can be concluded that the Aceh cattle farming business at Sapi Perkasa Farm is financially feasible and has promising potential for future development